2017
DOI: 10.1007/s10725-017-0349-1
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological and phytochemical responses of Salvia sinaloensis Fern. to drought stress

Abstract: Abstract\ud Salvia sinaloensis Fern. (sage) is a medicinal plant containing plant secondary metabolites (PSMs) with antioxidant properties. The current study investigated the effects of drought stress on S. sinaloensis morphological and ecophysiological traits, and active constituent production. Sage plants were cultivated in controlled conditions for 34 days and exposed to full irrigation as control, half irrigation, or no irrigation. Changes in growth index (G.I.), dry biomass, leaf water potential (LWP), ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 88 publications
7
36
0
Order By: Relevance
“…[184] Authors recommend the cultivation of S. lavandulifolia, T. capitatus and T. mastichina, because there are no differences in essential content, but if there is a water-saving rate of 30 %, while the essential oil content decreased in L. latifolia and S. sclarea plants under water deficit conditions. EO content and quality of L. angustifolia and S. fruticosa seemed to increase under water stress conditions in a study of Chrysargyris et al [185] This behavior is confirmed also for S. dolomitica, [186] S. officinalis, [187] S. sinaloensis [188] and some Greek Oregano populations. [189] Foliar application of salicylic acid under water stress conditions increase EO content on T. kotschyanus.…”
Section: S Algeriensismentioning
confidence: 72%
See 1 more Smart Citation
“…[184] Authors recommend the cultivation of S. lavandulifolia, T. capitatus and T. mastichina, because there are no differences in essential content, but if there is a water-saving rate of 30 %, while the essential oil content decreased in L. latifolia and S. sclarea plants under water deficit conditions. EO content and quality of L. angustifolia and S. fruticosa seemed to increase under water stress conditions in a study of Chrysargyris et al [185] This behavior is confirmed also for S. dolomitica, [186] S. officinalis, [187] S. sinaloensis [188] and some Greek Oregano populations. [189] Foliar application of salicylic acid under water stress conditions increase EO content on T. kotschyanus.…”
Section: S Algeriensismentioning
confidence: 72%
“…EO content and quality of L. angustifolia and S. fruticosa seemed to increase under water stress conditions in a study of Chrysargyris et al . This behavior is confirmed also for S. dolomitica , S. officinalis , S. sinaloensis and some Greek Oregano populations . Foliar application of salicylic acid under water stress conditions increase EO content on T. kotschyanus .…”
Section: Essential Oils: Very Old ‘Guys’ With Great Prospectsmentioning
confidence: 92%
“…The phytochemical characterisation of each sample was performed as previously described by Caser et al [48,49]. Briefly, the total anthocyanin content (TAC) was determined using the pH-differential method.…”
Section: Phytochemical Characterisationmentioning
confidence: 99%
“…Changes in root and shoot growth, as documented with altered root/shoot ratios for dry matter, were identified as an important mechanism to improve stress tolerance in crops. In a broader context, structural responses to stresses may be as important as physiological changes to improve overall susceptibility [26][27][28]. Drought impact on symbiotic interactions, such as nitrogen fixation in legumes [29], or on mycorrhizal symbiosis [30], is a further important mechanism to influence the overall performance of crop plants.…”
Section: Impact Of Global Change On Plant Nutrient Dynamicsmentioning
confidence: 99%